[A retained foreign body in the peritoneal cavity causing intestinal obstruction by intraluminal migration]. - Kalliakmanis, V; Pikoulis, E; Hitos, A; Karavokyros, I G; Gougoudi, E; Leppaniemi, A (Zentralbl Chir, 2007)
BACKGROUND: Forgetting a foreign body in the abdominal cavity is an unpleasant and avoidable situation. It usually occurs when the preventive protocols are not followed precisely. In such a case clinical consequences are unpredictable and relaparotomy may become necessary. CASE PRESENTATION: We present the case of a temporary intestinal obstruction six months after a transabdominal hysterectomy. Diagnostic workup revealed a laparotomy-gauze left in the abdominal cavity at the previous operation. Exploration showed that the gauze was actually located in the intestinal lumen. The inflammatory reaction elicited by the foreign body eroded the intestinal wall and allowed its intraluminal migration. The gauze moved distally due to peristalsis until it became trapped in the ileocecal valve causing obstruction. When it finally passed through the valve the obstruction was relieved. Intraoperative maneuvers advanced the foreign body further forward until it was removed transanally. CONCLUSION: The formal processes - counting the gauzes continually and double crossing the counting - must be kept in every laparotomy to avoid the unpleasant experience of gauze remaining in the peritoneal cavity. In such an unfortunate case traditional open surgery provides a safe solution to the patient's problem.
Keywords: Female; Foreign-Body Migration; Granuloma, Foreign-Body; Humans; Hysterectomy; Ileal Diseases; Intestinal Perforation; Intestinal Pseudo-Obstruction; Leiomyoma; Middle Aged; Omentum; Postoperative Complications; Radiography; Reoperation; Surgical Sponges; Uterine Neoplasms